New Medieval Literatures 18 - Ashe, Laura ca. 20./21. Jh; Knox, Philip 1988-; Lawton, David 1948-; Scase, Wendy 1955- (D.S. Brewer, 2018)
"An invigorating annual for those who are interested in medieval textual cultures and open to ways in which diverse post-modern methodologies may be applied to them." Alcuin Blamires, Review of English Studies
Title from publisher's bibliographic system (viewed on 31 Jul 2019)
Keywords: Literature, Medieval / History and criticism; Medievalism